Sustainability-linked bonds and their role in the energy transition - Andrea Maino (The Oxford Institute for Energy Studies, 2022)
Sustainability-linked bonds (SLBs) are emerging as a major sustainable financing instrument, particularly for companies in hard-to-abate sectors, which use SLBs as an alternative to more constraining financing instruments such as green bonds. For firms in economic sectors with large issuances of green bonds, such as financials and utilities, SLBs represent a complementary instrument to their sustainability financing portfolios. The main characteristic of SLBs is to embed financial incentives for firms to achieve specific sustainability targets. The 'margin rachet' structure typical of SLBs solves the inner tension in green bonds between project-level environmental benefit and company-wide alignment towards sustainability. Companies issue SLBs to signal their commitments to sustainability, raise cheaper financing, or both at the same time. However, the specific design of SLBs' financial incentives requires additional scrutiny from investors to distinguish the SLBs with reliable environmental characteristics from those with greenwashing motives.
Keywords: 330; financing instruments; sustainability targets; Sustainability-linked bonds (SLBs)